The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1038/labinvest.3700351
|View full text |Cite|
|
Sign up to set email alerts
|

Pericellular activation of proMMP-7 (promatrilysin-1) through interaction with CD151

Abstract: Matrix metalloproteinase-7 (MMP-7) (also known as matrilysin-1) is secreted as a proenzyme (proMMP-7) and plays a key role in the degradation of various extracellular matrix (ECM) and non-ECM molecules after activation. To identify the binding proteins related to proMMP-7 activation, a human lung cDNA library was screened by yeast two-hybrid system using proMMP-7 as bait. We identified a candidate molecule CD151, which is a member of the transmembrane 4 superfamily. Complex formation of proMMP-7 with CD151 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 46 publications
(61 reference statements)
3
67
0
Order By: Relevance
“…These include CD44 heparan sulfate proteoglycan (HSPG), cholesterol sulfate, and CD151. [18][19][20] Cholesterol sulfate is a component of lipid raft and CD151 is a transmembrane 4 superfamily protein that appears in a detergent-insoluble lipid-containing microdomain. To learn the possible docking mechanism of MMP-7, the behavior of the membrane-associated MMP-7(Asp-137) variant was analyzed in the presence of detergent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include CD44 heparan sulfate proteoglycan (HSPG), cholesterol sulfate, and CD151. [18][19][20] Cholesterol sulfate is a component of lipid raft and CD151 is a transmembrane 4 superfamily protein that appears in a detergent-insoluble lipid-containing microdomain. To learn the possible docking mechanism of MMP-7, the behavior of the membrane-associated MMP-7(Asp-137) variant was analyzed in the presence of detergent.…”
Section: Resultsmentioning
confidence: 99%
“…19 In contrast, CD151 anchors latent proMMP-7 onto the cell surface, but its affinity to interact with the active form of MMP-7 is relatively low. 20 Therefore, we hypothesized that association of the pro-form of MMP-7(Asp-137) variant to CD151 at the cell surface provides the opportunity for MMP-7 activation. The hypothesis was first examined by confocal microscopy to learn the distribution patterns of MMP-7 and CD151 in HSCs under nonpermeabilized conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, proteinases, such as MMPs, would likely be anchored to the cell membrane, thereby maintaining a locally high enzyme concentration and targeting their catalytic activity to specific substrates within the pericellular space. In addition to the membrane-bound MMPs, several examples of specific cell-MMP interactions have been reported, such as the binding of MMP-2 to the α v β 3 integrin (Brooks et al, 1996), MMP-1 to the α 2 β 1 integrin Stricker et al, 2001), MMP-9 to CD44 (Yu and Stamenkovic, 2000), and MMP-7 to surface proteoglycans (Yu and Woessner, 2000;Yu et al, 2002), cholesterol (Yamamoto et al, 2006), and CD151 (Shiomi et al, 2005). As suggested for CD44 (Yu and Stamenkovic, 2000) and the α 2 β 1 integrin ), these membrane anchors may act as accessory factors that mediate both pro-enzyme activation and binding of both substrate and proteinase, thereby increasing the probability of proteolysis (Fig.…”
Section: Compartmentalizationmentioning
confidence: 99%
“…3). For example, Shiomi et al (2005) reported that CD151, a tetraspanin, binds and activates proMMP-7. The authors speculate that CD151 causes a conformational change in proMMP-7, thus facilitating a spontaneous activation of proMMP-7 on a pericellular level.…”
Section: Compartmentalizationmentioning
confidence: 99%
See 1 more Smart Citation